Learning of Srintil's Creative Dance in an Effort to Improve Children's Cooperation Attitudes in Cepoko Hamlet, Canggal Village, Temanggung District - Thoha, Muchamad; Eka A N, R Agustinus (BELIA: Early Childhood Education Papers, 2021)
This study aims to determine whether learning creative dance creations can improve cooperation attitudes in children. This research approach uses a quantitative type of experimental approach. The research design used was one group pre-test post-test. The subjects of this study were 32 children aged 4-6 years in Cepoko Hamlet, Canggal Village, Candiroto District, Temanggung District. The data collection technique using a scale cooperation with a number of 50 item children valid previously in test try it in the field. Namely data analysis techniques with descriptive statistics and hypothesis testing by paried sample t-test. All of them are calculated using the SPSS IMB 20. The level of children's cooperation before learning dance creations of srintil shows in the very low category 16% low category 63% and 21% high category. After learning dance creations srintil increased to high category 59%, very high 28% and low category 13%. Based on calculations Paired Sample T-Test obtained t count 9.785 > t table 2,039 with significant value 0,000, then H o rejected and H a accepted, so it can be interpreted that there is an average difference between the results of pre-test and post-test with words Another influence is the learning of creative dance on the improvement of children's cooperative attitudes. the difference in significance value can be seen from the results of the Sig (2-tailed) value of 0.000 <0.05. This means that learning creative dance creations can improve children's cooperation attitudes.